Assessment on Regional Flood Risk Trend in Northern Region of Malaysia: Case Study in Muda River Basin, Kedah - Abd Halim, Marhanisa; Shakir Mohd Saudi, Ahmad; Khairul Amri Kamarudin, Mohd; Mahmud, Muaz; Bala Krishnan, Arvind; Nizam Mohd Isa, Khairul (International Journal of Engineering and Technology, 2018)
Flood is a major issue during monsoon season in Northern region of Malaysia especially in Muda River Basin. This study focused on the specific hydrology parameters that lead to the flood events in Muda River Basin, Kedah. There were 4 hydrologic parameters for thirty years of collected data from selected hydrology monitoring stations provided by Department of Irrigations and Drainage, Malaysia. The study applied Principal Component Analysis (PCA) and result shown that stream flow and suspended solid stand with highest correlation of coefficient variables with the changes of water level in the study area. Statistical Process Control (SPC) applied in this study was to determine the control limit for every selected parameter obtained from PCA. The Upper Control Limit value for water level reported from SPC analysis in the study area was 7.568m and starting from this level and above, the risk of flood is high to occur in the study area. This research proved that the flood risk model created in this study was accurate and flexible for flood early warning system at Muda River Basin.Â Â
Keywords: Principal Component Analysis; Statistical Process Control; Control Limit; Flood Risk Model.